As diretrizes curriculares nacionais para a educação escolar quilombola em Alcântara - Maranhão: análise do acesso do patrimônio cultural afro-brasileiro no currículo das escolas públicas em Alcântara - ALENCAR, Katia do Perpetuo Socorro Viana Santos de (2023)
This work intends to analyze how access to Afro-Brazilian cultural heritage is given in the curriculum of public schools in the city of Alcântara that serve students of quilombola origin, from the perspective of managers, teachers and coordinators who work in these schools, since such access is a obligation, as determined by law 10.639/2003, as well as the National Council of Education through opinion CNE/CP 3/2004 (which instituted the Curriculum Guidelines for the Education of Ethnic-Racial Relations and the Teaching of Afro-Brazilian History and Culture Brazilian and African). The chosen research methodology was qualitative and descriptive in nature. Questionnaires were applied to the target public, through systematic visits, and later, through the analysis of the data collected regarding the time spent in the classroom, home, knowledge/lack of knowledge of legislation related to Quilombola School Education, the activities performed in the school staff, the disciplines taught (in the case of teachers), the ways in which the heritage is made available and even space for sharing suggestions for the increment of this important theme in the classroom, a very interesting compilation is systematized to a better understanding of this junction of theory and practice that allow for an adequate management of appreciation and preservation of heritage. The guiding line of this study is Resolution number 8, of November 20, 2012, taking into account the portrayal of expressions of Afro-Brazilian Culture in school material, especially given the richness of ways of doing things, celebrations, festivities and others. traditional knowledge and cultural practices that structure the identity, history and memory of blacks in the school community. A significant rescue of the legislative evolution aimed at the education of black people is carried out as a necessary and fair reparation after centuries of massacre and contempt until it culminates in the aforementioned provisions, taking as support the Brazilian Federal Constitution of 1988, through the indication and referencing theories related to education as well as chosen methods to achieve the purpose of empowerment and affirmation of black identity within the context of quilombos.